Mapping of business culture research: a bibliometric perspective - Ach. Zuhri,; Rachmad Hidayat, (Technium Social Sciences Journal, 2023)
Research on business culture continues to experience development but no one has discussed it comprehensively. This research aims to visually study the mapping and research trends in the field of business culture on a national and international scale. This study uses bibliometric techniques with secondary data from Google Scholar. Analyze and visualize data using the VOSViewer program and the search result analysis function in Google Schoolar. This study analyzed 200 academic documents published from 2000 to 2023. Based on these results, the number of studies on business culture is still widely researched from 2000 to 2023. From that year the researchers also conducted research collaborations between researchers, but this research collaboration was only carried out in certain years, not continuously. individual researchers who do the most research on business culture, namely Cb Bhattacharya. Based on the business culture research theme map taken based on the title and keywords, it turns out that there are still no researchers who have conducted comprehensive and focused research on business culture, they only link culture with other topics such as different cultures and organizational culture, as well as business with other topics such as business strategy, business activity, business performance and business environment.